Ectotherms in Variable Thermal Landscapes: A Physiological Evaluation of the Invasive Potential of Fruit Flies Species - Boher, Francisca; Trefault, Nicole; Estay, Sergio A.; Bozinovic, Francisco (Frontiers in Physiology, 2016)
Climate change and biological invasions pose one of the greatest threats to biodiversity. Most analyses of the potential biological impacts have focused on changes in mean temperature, but changes in thermal variance may also impact native and invasive organisms, although differentially. We assessed the combined effects of the mean and the variance of temperature on the expression of heat shock protein (hsp90) in adults of the invasive fruit fly Drosophila melanogaster and the native D. gaucha in Mediterranean habitats of central Chile. We observed that, under these experimental conditions, hsp90 mRNA expression was higher in the invasive species but absent in the native one. Apparently, the biogeographic origin and niche conservatisms are playing a role in the heat shock response of these species under different putative scenarios of climate change. We suggest that in order to develop more realistic predictions about the biological impact of climate change and biological invasions, one must consider the interactions between the mean and variance of climatic variables, as well as the evolutionary original conditions of the native and invasive species.